Assessing the Quality and Value of Psychological Health Care in Civilian Health Plans Lessons and Implications for the Military Health System - Martsolf, Grant R. (RAND Corporation, 2015)
The Military Health System (MHS) provides care to many patients with psychological health conditions, but little is known about the degree to which care adheres to evidence-based clinical practice guidelines or improves patient outcomes. RAND described civilian health plans' approaches to measuring the quality of psychological health care as part of a larger effort to develop a framework for monitoring the quality of care in the MHS.